О. П. Моця, В. М. Ричка. Київська Русь: від язичництва до християнства - Боровський, Я. Є. (Український історичний журнал, 2025)
О. П. Моця, В. М. Ричка. Київська Русь: від язичництва до християнства. К.: Глобус, 1996. — 221 с.